A Survey on Reversible Image Steganography in Telemedicine - Ghosh, Bibek Ranjan; Banerjee, Siddhartha; Singh, Subham Kr; Gangopadhyay, Shreyas (International Journal of Computer Sciences and Engineering, 2022)
Electronic patient record (EPR) storage and transmission is an integral part of modern healthcare system. Steganography comes into play when the medical image becomes a potential storage of patient information. Generally steganographic techniques give higher importance to the perfect recovery of secret data than the actual reconstruction of the original image. But in medical system the actual reconstruction of the original medical image is importance as this is the primary source of disease understanding. Hence in this context reversible steganography plays an important role in telemedicine field in storing, maintenance and communication of electronic patient record within the image itself, so that where a doctor located at a geographically remote location can diagnose a patient on the basis of a medical image generated elsewhere with confidence. In this paper we have studied some elegant techniques for reversible medical image steganographic techniques and compare their performances.